DIVERSITY ANALYSIS OF DIFFERENT ACCESSIONS OF ALOE BARBADENSIS MILL. (SYN. ALOE VERA .L) COLLECTED FROM RAJASTHAN USING RAPD MARKER SYSTEM - CHANDRA, DINESH; CHOUDHARY, PREETI (The Bioscan, 2013)
Under a survey and collection programme of National Agricultural Technology Project (NATP), various accessions of Aloe vera were collected from Rajasthan and Gujarat. In this study 10 Accessions from Rajasthan were characterized through RAPD. RAPD revealed 32.08 per cent polymorphic bands detecting 11.9% average diversity among the accessions studied. The diversity ranged from 4.3% to 20.4%. The primers like OPG-15 having high PIC value (0.346) are considered important for diversity studies, whereas, OPG-14 have highest Discrimination index (0.911) and may be used for identification of different accessions. The clustering analysis resulted in the formation of one group, only consisting of eight accessions while Nagour collections remained out of cluster. The diversity pattern did not show any correlation with the site of collection indicating that original introduction consisted of small sample size its spread was random.